Experiments with heating and cooling - Thomas, Isabel (Chicago, Illinois Heinemann Raintree, 2015)
"Explore the world of heating and cooling with engaging text, real life examples and fun step-by-step experiments. This book brings the science of temperature to life, explaining the concepts then getting kids to be hands-on scientists!"--
A gift from book Africa
Science
1 2 13 15
Keywords: Heat -- Experiments; Thermodynamics -- Juvenile literature